Integration of Building Information Modeling (BIM) and Value Engineering in Construction Projects: A Bibliometric Analysis - Baarimah, A.O. (Institute of Electrical and Electronics Engineers Inc., 2021)
Due to a variety of issues and inefficiencies during the construction process, construction projects require a substantial amount of money and resources. Controlling the cost is a critical step in ensuring the success of project and increasing its value. Value Engineering (VE) has been gaining increasing attention from stakeholders in construction projects to reduce the overall costs. Building Information Modeling (BIM) may have a great potential to assist in VE from the early stage of project inception as a commonly accepted intelligent technology. Various studies have been undertaken on the integration of BIM and VE to make use of the advantages of this integration and control project cost and optimization. However, there has been no attempt of scientometric analysis to explore the holistic understanding of the current state of integration of BIM and VE research. The purpose of this research is to carry out a bibliometric analysis of the available BIM and VE literature and to provide a picture of the research status from 2007 to September 2021. There were 46 documents extracted from the database of Scopus. VOSviewer tool was used to visualize the literature contained through countries, scientific journals, and keywords. The outcomes showed that 'Cost Engineering', 'Earned Value Management', 'Structural Design', 'Decision Making' and 'Sustainable Development' were lately risen to prominence as mainstream topics associated with this field and piqued the curiosity of academics, which may represent future research possibilities as well. Furthermore, based on the most keywords frequently utilized, three important research domains linked with BIM and VE have been identified, including 'Architectural Design', 'Project Management', and 'Budget Control'. Accordingly, the explanations related to research outcomes, recommendations for future studies have been provided on the integration of BIM and VE. Â© 2021 IEEE.